Interfacial Polycondensation Synthesis of Optically Sensitive Polyurea Microcapsule - Weidong Lai; Xinzheng Li; Huiqing Liu; Lu Han; Yajun Zhao; Xiaowei Li (Journal of Chemistry)
TMPTA prepolymer resin and photoinitiators of ITX/TPO had been encapsulated in core-shell structured microcapsules as optical responding ingredients based on interfacial polycondensation method, and polyurea structured microcapsule shell had been formed on the sheared O/W interface. The synthesized microcapsule had regular core-shell structure with the diameter of about 0.455 μm and shell thickness of about 40 nm. UV-visible absorption spectra indicated that the encapsulated ITX and TPO photoinitiators could efficiently absorb UV irradiation. Under exposure, the C=C bonds absorbance of the microencapsulated TMPTA decreased rapidly and then nearly unchanged during further exposure after 30 s. This implied that the optical response was achieved by C=C bond cleavage of TMPTA monomer initiated by the photoinitiator radicals, to form network polymers in microcapsules. The relative crosslinking rate was about 50%. Due to core polymer formation, the thermal phase change temperature of exposed microcapsules was narrowed and ranged from 105 to 205°C, compared with that from 125 to 260°C of unexposed microcapsules. Furthermore, the image density decrease at longer irradiation time had also verified the optical responding function of the synthesized microcapsules in macroscopic viewpoint.